Penegakan Hukum Lingkungan Melalui Pertanggungjawaban Perdata - Serlika Aprita; Hasanal Mulkan; Desni Raspita; Muhamad Fakhri (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
This writing is titled “Enforcement Of Environmental Law Through Civil Law Aspects” that aims to know and understand how the environment through the law enforcement aspects of civil law. In this paper the authors use the method of normative research. The results of the analysis are obtained, is that the law enforcement aspects of the environment through civil law can be done through the courts and the line outside the court.